PENGUATAN SUMBER BELAJAR IPS MELALUI LITERASI SEJARAH DAN BUDAYA YOGYAKARTA DI MUSEUM ULEN SENTALU - Eldi Mulyana; Alni Dahlena; Slamet Nopharipaldi Rohman (Journal Civics And Social Studies, 2022)
The existence of culture and history in museums as a place to store collections of historical objects often gives the impression that the museum is an ancient building, dark and unkempt. Meanwhile, the new paradigm in museum management is that museums are no longer just places to store historical objects, but need to present collections in attractive packaging so that visitors are interested in coming back to the museum.  The aim of this research is to strengthen the use of the Ulen Sentalu Museum as a social studies learning resource, because the overall concept of the Ulen Sentalu Museum is more modern compared to other museums in Indonesia. This research method is a qualitative method using interview, observation and documentation study data collection techniques. Data analysis techniques include data collection, data presentation, data reduction and data verification.  The results of this research are (1) the cultural and historical values ​​of the Ulen Sentalu Museum in embedding existing philosophical values, (2) the cultural and historical values ​​related to the rules and regulations in the Ulen Sentalu Museum are used as a source of social studies learning. In this way, it can be used as part of the culture and history contained in the Ulen Sentalu Museum and used as a source of social studies learning as part of educational literacy.